Are CMV-predictive scores in inflammatory bowel disease useful in clinical practice? - Störkmann, Hedwig; Rödel, Jürgen; Stallmach, Andreas; Reuken, Philipp A. (Zeitschrift für Gastroenterologie, 2020)
Background Concurrent cytomegalovirus (CMV) in inflammatory bowel disease (IBD)-related colitis is an important scenario associated with high rates of colectomy and other morbidity. Due to the low incidence of CMV, testing of all patients is associated with an unacceptably high consumption of resources and delay in treatment. Therefore, several predictive scores have been developed to identify patients at risk for a CMV infection.Methods We performed a retrospective single center study in a German University hospital including all IBD patients with available data on CMV-PCR analysis in whole blood between 2010 and 2018 and evaluated 2 prognostic scores for CMV infection for their diagnostic accuracy.Results In the study, 907 patients with IBD and CMV-PCR were identified. Of them, 21 patients (2.3 %) had a positive CMV-PCR (≥ 1000 copies/mL), 14 of them in ulcerative colitis and 7 in Crohn’s disease. The Berlin Score identified 667 patients (73.1 %) as potentially CMV-positive, resulting in a positive predictive value of 2.5 % and a negative predictive value of 98.3 %. In contrast, the Münster Score identified 60 patients as potentially CMV-positive, resulting in a PPV of 20 % and an NPV of 99.4 %.Conclusions Scoring systems can help to identify patients at risk for a CMV infection and minimize resource consumption and delay in treatment. Due to low incidence, a 2-step-algorithm, consisting of the Münster Score followed by a CMV-PCR if the score indicates a CMV infection, is preferable.
Keywords: CMV; Ulcerative Colitis; Crohn’s Disease